EFFECT OF MOTIVATION ON THE WORK PERFORMANCE AND DISCIPLINE OF GOVERNMENT EMPLOYEE (Study at : BAPPEDA Malang) - Yoga Arsyenda; Abidin Lating (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Motivation and discipline is directly related to the performance of employees. Motivation and discipline are felt directly by the employee performance can degrade or improve employee performance. Employees feel motivated and disciplined to work obtained will result in increased overall performance of an institution. The study was conducted at BAPPEDA Malang. This study aimed to determine the effect of work motivation, work discipline, and which of the two factors that greatly affect the performance of employees. The research method used is quantitative research. Data obtained from the interviews using questionnaires. The results showed that work motivation and work discipline has effect on employee performance. Where the results can also be seen that the work discipline greater influence on employee performance at BAPPEDA Malang. Keywords: work motivation, work discipline, and employee performance